Distributed Solution of Road Lighting Problem Over_x000D_ Multi-Agent Networks - CİHAN, ONUR (My University, 2020)
In this study, we consider the solution of the road lighting problem by distributed algorithms over multi-agentnetworks where the objective is to determine the powers of the lamps that provide the desired road lighting levelfor a given road profile. The road is modeled as multiple road sections each with a length of 50 meters where alighting pole is located in the middle of each section. Under given assumptions, the illumination levels of the roadsections are expressed as linear functions of the powers of the lamps. When the processing units in the lightingpoles can communicate wirelessly with the neighboring processing units and make simple calculations, it is shownthat the power levels of the lamps that provide the desired lighting level for each road section can be calculated ina distributed manner. Finally, the model and the proposed solution has been verified by a numerical example.

Bu çalışmada, verilen bir yol profili için yol aydınlatma düzeyinin istenilen değerlerde olmasını sağlayan lamba_x000D_ güçlerini belirleme probleminin çok etmenli sistemler üzerinde tanımlanan bir algoritma ile dağıtık çözümü ele_x000D_ alınmıştır. Söz konusu yol, ellişer metrelik uzunluğa sahip bölümler halinde modellenmiş ve her bir bölümün_x000D_ ortasında bir aydınlatma direği konumlandırılmıştır. Yapılan varsayımlar altında yol bölümlerinin aydınlanma_x000D_ düzeyleri, lambaların güçlerinin bir doğrusal fonksiyonu olduğu ifade edilmiştir. Aydınlatma direklerinde bulunan_x000D_ işlem birimlerinin kendilerine yakın olan direklerdeki işlem birimleriyle haberleşebildiği ve basit hesaplamalar_x000D_ yapabildiği durumda, yolun istenilen bir aydınlık seviyesine sahip olabilmesi için gerekli olan lamba gücü_x000D_ seviyelerinin, dağıtık olarak hesaplanabildiği gösterilmiş ve sayısal sonuçlar ile modelin ve çözümün geçerliği_x000D_ doğrulanmıştır.
Yol Aydınlatma Probleminin Çok Etmenli Ağlarda Dağıtık Çözümü